2015
DOI: 10.1002/mbo3.242
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of seven Mycoplasma hyosynoviae strains

Abstract: Infection with Mycoplasma hyosynoviae can result in debilitating arthritis in pigs, particularly those aged 10 weeks or older. Strategies for controlling this pathogen are becoming increasingly important due to the rise in the number of cases of arthritis that have been attributed to infection in recent years. In order to begin to develop interventions to prevent arthritis caused by M. hyosynoviae, more information regarding the specific proteins and potential virulence factors that its genome encodes was need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Although this finding is not correlated with clinical outcome, it suggests that the tonsil might be the primary reservoir for long-term carriage [71012]. Factors driving M. hyosynoviae tropism for the tonsil rather than the nasal cavity are currently unknown [111]. Given that long-term carriage in the tonsil is the likely source of joint infection via septicemia within an animal, it is possible that a source (tonsil)-and-sink (joint) infection dynamic could explain the infection process [914].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this finding is not correlated with clinical outcome, it suggests that the tonsil might be the primary reservoir for long-term carriage [71012]. Factors driving M. hyosynoviae tropism for the tonsil rather than the nasal cavity are currently unknown [111]. Given that long-term carriage in the tonsil is the likely source of joint infection via septicemia within an animal, it is possible that a source (tonsil)-and-sink (joint) infection dynamic could explain the infection process [914].…”
Section: Discussionmentioning
confidence: 99%
“…Although the disease risk factors are not fully understood, M. hyosynoviae -associated arthritis is often reported to occur upon exposure to environmental stressors such as temperature fluctuation, increased stocking density, and commingling of non-litter mates [15]. However, the virulence determinants and host pathways that converge to the occurrence of the disease phenotype typically seen in field cases are still not understood [111]. Although M. hyosynoviae -associated disease has been experimentally reproduced before [71218], this study was conducted to determine if distinct clinical isolates could have different disease phenotypes, and which inoculation route and infectious dose combination would be more robust to reproduce them.…”
Section: Introductionmentioning
confidence: 99%
“…As mycoplasma genome sequences became available in public databases, a growing number of genomic elements were identified as prophage genomes or phage-like sequences [ 56 , 60 , 61 , 63 , 64 , 66 , 70 ]. Consistent with our previous observations with MICEs (see above), most existing computational tools dedicated to identifying prophage sequences in bacterial genomes are poorly efficient in distinguishing viral patterns from mycoplasma sequences [ 71 ].…”
Section: Mycoplasma Viruses and Prophagesmentioning
confidence: 99%
“…BLASTP analyses revealed that 10 of the 18 CDSs identified in φMFV1 exhibited some similarity with their counterparts in φMAV1 [ 63 ]. Here, database searches of available genomes revealed prophage sequences that closely resemble φMAV1 or φMFV1 and were broadly distributed among human and animal mycoplasma species ( Figure 4 ) These included the M. hominis φMHoV1 [ 64 ], as well as several M. hyosynoviae -derived phages [ 66 ]. In this highly conserved genomic framework are several regions of higher heterogeneity ( Figure 4 ).…”
Section: Mycoplasma Viruses and Prophagesmentioning
confidence: 99%
“…The genomes of M. hyosynoviae strains encode virulence-associated protein D (VapD) [80]. The latter has been assigned a number of different functions in virulence mechanisms including acting as a toxin [81].…”
Section: Apoptosis and Toxin Releasementioning
confidence: 99%